2007
DOI: 10.1098/rsif.2007.0214
|View full text |Cite
|
Sign up to set email alerts
|

Recent network evolution increases the potential for large epidemics in the British cattle population

Abstract: Following the foot and mouth disease epidemic in Great Britain (GB) in 2001, livestock movement bans were replaced with mandatory periods of standstill for livestock moving between premises. It was anticipated that these movement restrictions would limit each individual's contact networks, the extent of livestock movements and thus the spread of future disease outbreaks. However, the effect of behaviour changes on the global network in adapting to these restrictions is currently unknown. Here, we take a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
112
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 18 publications
3
112
0
1
Order By: Relevance
“…Interface 13: 20160166 variation in the degree distribution, such as small-world networks, may have insufficient variation to discern differences in connectivity among infected and uninfected nodes. Given that many real-world networks have small-world properties [40,[51][52][53][54], it is important to take into account network structure and pathogen prevalence when selecting appropriate statistical methods. Our results suggest that the k-test performs well across a diversity of scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Interface 13: 20160166 variation in the degree distribution, such as small-world networks, may have insufficient variation to discern differences in connectivity among infected and uninfected nodes. Given that many real-world networks have small-world properties [40,[51][52][53][54], it is important to take into account network structure and pathogen prevalence when selecting appropriate statistical methods. Our results suggest that the k-test performs well across a diversity of scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Canada, Britain, Denmark, Sweden and some other countries' research results showed that livestock and poultry movement plays an important role in the spread of animal disease. The researchers also suggested that in the management of animal movements we should pay attention to the following points: 1) Mixed degree, which means the mixed level of directly infected animals and indirectly infected animals; 2) Dispersion degree, that is, one buys infected animals from another seller, then the infected animals involved in trading become scattered in the whole group of animals; 3) Complicated sources degree, namely, the buyer will buy animals from a number of sources [1][2][3][4][5][6][7][8]. However, the relevant research in China is scarce [9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of professional knowledge and effective means to assess disease risks in the process of cattle movements, most farmers can't catch the key points in disease prevention, and constantly introduce new disease or exogenous disease, which makes a serious threat to livestock health and huge loss to production [1,7,9,[10][11][12]. In order to reduce the risks for spread of disease in cattle movements, through describing the cattle markets and analyzing the risks in the process of cattle movements, this article wanted to provide the advice about the prevention of animal disease to farmers, practitioners and other related staffs in cattle movements and the reference to establish the disease spread mathematical model and dynamic model [3].…”
Section: Introductionmentioning
confidence: 99%
“…From the Cattle Tracing System (18) we have individual records of the movement of cattle between the 150,000 farms, markets, and slaughterhouses in Great Britain (SI Text). Both of these movement datasets can be conceptualized as relatively sparse networks; the analysis of such networks yields a wide range of important information on the pattern of movements and the structure of the populations (19,20). Here, however, we are interested in how such movements lead to the percolation of infection through the population, and we show that great care is needed if realistic rates of spread are to be predicted.…”
mentioning
confidence: 99%